Digital health literacy among older adults in China: a cross-sectional study on prevalence and influencing factors - Zhang, Xingxia; Yuan, Yongqing; Jiang, Jie (Frontiers in Public Health, 2025)
BackgroundThe rapid integration of digital technologies into healthcare has emphasised the importance of digital health literacy (DHL) in enhancing health outcomes. Despite the increasing adoption of the internet among older adults in China, disparities in eHealth literacy persist, necessitating urgent investigation.ObjectiveThis study aimed to investigate the status and predictors of DHL among older adults in Sichuan Province, China.MethodsA cross-sectional survey was conducted from October to December 2024 using a multistage stratified sampling method. Data were collected using the Chinese version of the eHEALS questionnaire. Univariate and multivariable binary logistic regression analyses were performed to identify predictors of DHL, adjusting for sociodemographic, health-related, and internet use variables.ResultsA total of 1,202 valid responses from adults aged 60 years and over were analysed. Only 30.45% (n = 366) of participants met the eHEALS threshold (mean total score: 22.30 ± 10.62). Sociodemographic factors (residence and gender), internet behaviours, and training experience were all significantly associated with DHL among older adults.ConclusionThis study reveals suboptimal digital health literacy among older adults in China, driven by rural–urban disparities, gender gaps and limited digital engagement. In future, interventions tailored to specific needs, such as community-based training, telemedicine promotion and family-supported digital education, will be critical in bridging this gap.